Consequence of loan loss provisions on earnings management behaviour: A study on the best African commercial banks - T. S. Desta (South African Journal of Business Management, 2017)
This study aimed at analysing the relationship between loan loss provision (LLP) and earnings management in the African commercial banks. The study selected the 11 banks among the 32 best commercial banks as identified by the Global Finance Magazine in 2014. These 11 banks are available online in the Bureau van Dijk Bankscope data and helped observe 10 years (2004-2013, of which 2003 is the base) financial statements, which accounts 34.38% of the 32 best banks. Accounting data derived from 11 years audited financial statements were used; 110 bank-year observations. A two stage panel regression, partial and pairwise correlation, and independent t-test were applied in order to analyse the relationship between the discretionary LLP (DLLP) and earnings management. Accordingly, the study found that loan to deposit (LD), return on asset (ROA), and earnings before tax and provision (EBTP) significantly influence the DLLP. Besides, banks with high premanaged earnings and well-capital more indulge in the DLLP. The study supports empirical findings on income smoothing and external financing hypotheses, but not the capital management hypothesis. Finally, further research on this topic is recommended, among others, by taking relatively large bank-year observations.
Keywords: 650